2023
DOI: 10.58734/plc-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of situational contexts and occupational roles on listeners’ judgements on accented speech

Abstract: Much language attitude research has demonstrated that people make biased judgements based on speakers’ language choice and accent. However, the influence of occupational context on listeners’ perceptions of accented English is largely unknown. This verbal guise study examined the extent to which academic contexts and workforce-related professional contexts affect listeners’ judgements of accented speech. Results revealed that simulated contexts made a significant difference in listeners’ perceptual judgements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Specifically, Brazil (1997) and later Pickering (2018) suggested that one's use of suprasegmental features (e.g., intonation, prominence, pitch height) may affect the process of meaning making in interaction and thus affect its outcome. This link between suprasegmental or prosodic features of speech has been made in several recent studies that investigated L2 English users' production of speech acts (e.g., Kang et al, 2023;Taguchi et al, 2022). From a perceptual perspective, Sydorenko et al (2014) examined three L1 English speakers' appropriateness perceptions in L2 requests with a mixed-methods approach, where the raters first listened to the requests produced by L2 speakers, rated them in terms of pragmatic appropriateness, and provided explanations to justify their ratings.…”
Section: Speech Perception Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Brazil (1997) and later Pickering (2018) suggested that one's use of suprasegmental features (e.g., intonation, prominence, pitch height) may affect the process of meaning making in interaction and thus affect its outcome. This link between suprasegmental or prosodic features of speech has been made in several recent studies that investigated L2 English users' production of speech acts (e.g., Kang et al, 2023;Taguchi et al, 2022). From a perceptual perspective, Sydorenko et al (2014) examined three L1 English speakers' appropriateness perceptions in L2 requests with a mixed-methods approach, where the raters first listened to the requests produced by L2 speakers, rated them in terms of pragmatic appropriateness, and provided explanations to justify their ratings.…”
Section: Speech Perception Constructsmentioning
confidence: 99%
“…In speech perception studies, a dominant line of research has explored listener perceptions of accented speech in terms of constructs like accentedness, comprehensibility and acceptability, and linguistic features that contribute to these constructs (e.g., Isaacs & Trofimovich, 2012). Research has suggested that diverse linguistic factors, including pronunciation, lexicogrammar, and discourse organization are related to listeners' perceptual judgments of L2 speech (e.g., Gass & Varonis, 1984;Isaacs & Trofimovich, 2012;Kang et al, 2023;Saito et al, 2017). Thus, moving beyond linguistic features, scholars within the domain of L2 speech perception have argued that communicative competence entails more than one's use of lexical and grammatical structures, emphasizing the role of acoustic features of speech in listeners' perceptions of one's production (Bachman & Palmer, 2010;Hymes, 1971).…”
Section: Speech Perception Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al found that the situational contexts in which speakers are heard play a pivotal role in influencing how listeners perceive their accented speech. When speakers are heard in service-oriented occupational settings, they are judged to be much more intelligible and acceptable compared to when they are heard in academic environments [ 9 ]. Bresnahan et al argue that ethnic identity could influence the effect of accent.…”
Section: Introductionmentioning
confidence: 99%